Adversities and opportunities in the production of Oscypek cheese and in the traditional grazing system of Polish mountain sheep - Kuznicka E.; Rant W.; Radzik-Rant A. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The traditional grazing system of sheep in the Polish Mountains is mainly aiming at preserving the folkloristic customs and the natural landscape. Sheep pasturing and milking is linked to the hand-made processing of many regional produces. Among them, the Oscypek cheese is still produced in a traditional way, unchanging over 500 years. Oscypek was the only one produce from Poland which has been showed at the Slow Food Hall of Taste (Salone del Gusto). Unfortunately, it did not obtain the European PDO certification. The registration as Protected Designation of Origin brand should help producers to achieve profitable prices and increase the profitableness from the sheep production systems in the mountainous regions.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)